(untitled) (Journal of Plant Disease Sciences, 2021)
In-vitro efficacy of different fungicides were evaluated against Macrophomina phaseolina. Among the fungicides tested,100 per cent average mycelial growth inhibition was recorded with carbendazim, followed by metalaxyl 08 % + mancozeb 68 % (92.27 %) and mancozeb alone (91.67 %). Fungicides, propineb and copper oxy chloride were found comparatively less effective with minimum average mycelial inhibition of 59.56 per cent and 56.75 per cent, respectively. Whereas amongst sevendifferent bio-agents tested Trichoderma harzianum was found more effective and statistically significant over other biocontrol agents in inhibiting the mycelial growth (80.26%) of Macrophomina phaseolina followed by Trichoderma viride (77.79%) and rest of other treatments.While amongst nine botanicals tested, significantly highest mycelial growth inhibition (79.36%) was recorded with garlic (Allium sativum L.) followed by onion (Allium cepa L.) 75.33 per cent. The least mycelial growth inhibition of was noticed with Gokhru (Xanthium strumarium L.) 02.98%.